IMPLEMENTASI KESESUAIAN SISTEM INFORMASI PENGENDALIAN PERSEDIAAN BARANG DAGANG PADA SAKTHU MART DENGAN STANDAR COSO - Erlando Devianto, Nielson; Oktalina, Gayatria; Zamhari (STIE IBEK Pangkalpinang, 2022)
This study aims to determine the implementation of internal control of merchandise inventory at Sakthu Mart with internal control components according to the Committee of Sponsoring Organization of Treadway Commission (COSO). The importance of this research is to make Sakthu Mart better understand and be able to implement control over merchandise inventory that supports Sakthu Mart operations. Case studies are a type of this research. This study uses a comparative descriptive method with a qualitative approach, namely comparing with theories and then describing the results of the analysis in the form of words and language. The technique of collecting data is by interviewing the participants (employees of Sakthu Mart) and the owner of Sakthu Mart. The results of interviews from the study indicate that the internal control of Merchandise Inventory implemented by Sakthu Mart is appropriate and some is not in accordance with the theory components of internal control of trading inventory based on the Committee of Sponsoring Organization of Treadway Commission (COSO). The COSO components, namely internal control, risk assessment, activities, as well as information and communication, are almost perfect because most of them have been implemented by Sakthu Mart, while the monitoring component is in accordance with and running according to COSO standards.